Performances Analysis on Power Quality Problems Mitigation by using Unified Power Quality Conditioner (UPQC) - May Phone Thit; Soe Soe Ei Aung; Han Su Yin (JAREE (Journal on Advanced Research in Electrical Engineering), 2019)
Nowadays, power quality is one of the major problems in electric power distribution system. The poor power quality at distribution level can affect the operation and performance of sensitive and critical loads. In the distribution systems, poor power quality results in various problems such as higher power losses, harmonics, sag and swells in the voltage, and poor power factor., etc. Unified Power Quality Conditioner (UPQC) is the only versatile device which can mitigate several power quality problems related with distribution system. A UPQC that combines the operations of a Distribution Static Compensator (D-STATCOM) and Dynamic Voltage Restorer (DVR) together with the shunt and series active control devices. UPQC can solve the problems related to the voltage/current harmonics, voltage sag/swell and unbalance in distribution system. To evaluate the performance improvement in the system, a model of UPQC is developed in MATLAB/SIMULINK with a typical distribution network. In this research, UPQC is applied for power quality enhancement of Myaungtagar industrial distribution substation, Myanmar. Enhancements in power quality by UPQC are evaluated under maximum load condition.Keywords: harmonics, power quality, series controller, shunt controller, UPQC.